Prinsip dan Karakteristik Bahan Ajar Pendidikan Agama Islam - Hafid Muslih; Ghina Ulpah; Miftahul Huda; Mukhlishah Mukhlishah; Muhtadin Muhtadin (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2024)
Islamic Religious Education (PAI) has an important role in shaping the character and noble character of students. Quality PAI teaching materials are one of the determining factors for successful learning. This study aims to describe the principles and characteristics of effective PAI teaching materials. This research uses a qualitative approach with a literature study method. Data were collected from books, scientific journals, and other reliable sources. The data were analyzed with descriptive analysis techniques and then selected and compared and classified, and the final stage drew conclusions according to the truth. The results of the study found that PAI teaching materials are learning tools designed to assist teachers and students in achieving the learning objectives of Islamic Religious Education (PAI). Good and quality PAI teaching materials will help students understand Islamic teachings more easily and explore, as well as practice them in everyday life. In addition, the characteristics of PAI teaching materials that are different from teaching materials in general make additional capital for the realization of the ideals expected by Islamic Religious Education and Budi Pekerti to students. By paying attention to these principles and characteristics, Islamic Religious Education teaching materials can help students to achieve the expected learning objectives, namely to become a Muslim person who has faith, devotion, and noble character.